Antioxidant Activity of Ethanol Extracts from Tridax procumbens - Zhang, Jing; Yuan, Ke; Zhou, Wen-Long; Zhou, Jian; Yang, Ping (Asian Journal of Chemistry, 2011)
Tridax procumbens growing in subtropical areas of China as invasive plant, was investigated for total flavonoids (TF) content and antioxidant activity in the present study. Total flavonoid content was measured according to the NaNO2-Al(NO3)3 method and antioxidant activity was assessed using four methods: DPPH (1,1-diphenyl-2-picryl-hydrazyl), ABTS (2,2'-azinobis-(3- ethylbenzothiazoline-6-sulfonic acid), FRAP (ferric reducing antioxidant power) and TRP (the reducing power) assays. In addition, in present study, correlation analysis was made. The obtained results revealed that ethanolic extracts from Tridax procumbens owned better free radical scavenging activity and reducing power and showed varying degrees of efficacy in a dosedependent manner in all the four assays. The sequence of antioxidant activity of ethanolic extracts from different parts of Tridax procumbens was as follows: flower > stem > the whole grass > leaf. The ethanolic extract from the whole grass of Tridax procumbens was added to Diaion HP- 20 macroporous resin column, then the resin was washed by distilled water to get rid of impurity and M20, M40 and M60 was eluted by 20, 40 and 60 % methanol individually. The sequence of antioxidant activity of these eluates was as follows: M20 > M40 > M60, total flavonoids content and the results of antioxidant activity had significant correlation. The present study suggested that Tridax procumbens could be a potential rich source of natural antioxidants.